DISORIENTATION IN THE IMPLEMENTATION OF COMMUNITY WAQF IN THE VILLAGE OF AEK GOTI, DISTRICT OF SILANGKITANG, LABUHAN BATU SELATAN REGENCY - Dwi Prayetno; Johan Septian Putra (UIN Mahmud Yunus Batusangkar, 2024)
The implementation of waqf in Aek Goti Village, Silangkitang District, involves the community consistently requesting compensation for the properties they have donated to the trustees (nadzir) and the community. Subsequently, the nadzir and community provide monetary compensation to the waqif as a form of social assistance, which has become a common practice due to its perceived benevolence. However, this practice raises discrepancies in Islamic jurisprudence, as it contradicts Islamic law and regulations governing waqf. This article employs qualitative methods such as interviews and field research to investigate this issue. The author conducted direct field visits, engaged with informants relevant to the research problem, and gathered both written and oral data. Data analysis was conducted using inductive, descriptive, and comparative methods, integrating theory with societal findings into a cohesive framework.The research findings indicate that proper implementation of waqf in accordance with Islamic law requires adherence to its fundamental principles and conditions for validity, ensuring that the charitable act is recognized as a worshipful deed by Allah SWT. However, in Aek Goti Village, Silangkitang District, the waqf practices observed are considered fasid (defective) because they deviate from religious guidelines. Specifically, the waqif's request for compensation, ostensibly to support their family, undermines the sanctity of waqf. Moreover, the compensation offered is significantly lower than the actual value of the waqf property, some of which was intended for charitable purposes.